(3GOGQI GdSdhc GdJfXjejs - (3fGUQ eMeO(B, (3GdYOjdjs ((3GdQjGV(B:s (3OGQ eQGeQ(B,s, 2001)
(3GdSdhc GdCfSGfj ,GdOhGaY hGdMhGaR hGdQVG GdhXjaj , VZhW GdYed ,GdeOjQhf hVZhW GdYed ,GdbjGOI GdEOGQjI ,Sdhc GdLeGYI EOGQI GdfRGY aj efXeGJ GdYed ,HfGA aQjb GdYed ,Jbhje GdCOGA,EYOGO hEJNGP GdbQGQ GJ ,GdJWhjQ GdJfXjej (B.s
Keywords: (3EOGQI hJfXjes; (3GOGQIs; (3GdSdhcs